Verbal protocol analysis of on-the-job tasks for Air traffic controllers: a cognitive approach for the systematic design of a training program in the aviation industry - Philip Nuli, Anding; Peter, Songan (1998)
A cognitive task analysis was conducted using verbal protocol analysis to try to understand how the approach air traffic controller carries out the task of providing safe, orderly and expeditious flow of air traffic. The verbal protocols represent the verbal communication and explanation given by the approach air traffic controllers as they carry out their tasks. The verbal protocols were analysed based on two protocol representations, knowledge states and the conceptual operators. This study, which was carried out at a relatively busy airport, identified nine conceptual operators and four knowledge states associated with the job of the approach air traffic controller. These knowledge states and conceptual operators were then used to develop the verbal protocol coding scheme and a simplified mental model for the approach air traffic control. This study demonstrated that verbal protocol analysis was an extremely useful method for identifying thinking processes and for studying superior performance. This cognitive approach systematically identifies the knowledge and skills that should be incorporated into the curriculum of a training program for air traffic controllers.